High-fatigue-resistance solder based on SnAgCu alloy
By adding In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B to the SnAgCu alloy, the thermal stress problem of Sn-Ag-Cu lead-free solder alloy during ambient temperature changes is solved, and its mechanical fatigue resistance and temperature shock fatigue resistance are significantly improved.
Patent Information
- Application Number
- CN202411986610.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Sn-Ag-Cu lead-free solder alloys are prone to thermal stress when the ambient temperature changes, resulting in cracks or fractures of the solder joints, and the difference in the thermal expansion coefficient with the matrix material leads to additional stress, affecting its temperature impact fatigue resistance.
The components of In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B are added to the SnAgCu alloy, and the strength and toughness of the solder joints are improved by affecting the microstructure of the solder joints and the types and quantity of intermetallic compounds, and by slowing the growth rate of intermetallic compounds, the thermal fatigue crack propagation rate is reduced.
The mechanical fatigue resistance and temperature shock fatigue resistance of SnAgCu alloy are significantly improved, the thermal stability and creep resistance of the solder joints are improved, and the mechanical fatigue life of the solder joints is extended.
Smart Images

Figure CN119566613A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soldering materials, and in particular to a high fatigue resistance solder based on SnAgCu alloy. Background Art
[0002] Sn-Ag-Cu lead-free solder alloy has relatively good soldering process performance, with tensile strength close to or higher than Sn-Pb eutectic solder, and relatively high yield strength, shear strength, impact toughness and creep resistance. This makes it perform well when subjected to mechanical stress and can meet the requirements of various complex and harsh working environments. Compared with traditional Sn-Pb solder, Sn-Ag-Cu lead-free solder alloy does not contain lead, so it is more in line with environmental protection requirements and has less impact on human health and the environment.
[0003] However, the melting point of Sn-Ag-Cu lead-free solder alloy is relatively high. During welding and service, when the ambient temperature changes, large thermal stress will be generated inside the solder joint. These thermal stresses may cause cracks or fractures in the solder joint, thus affecting its resistance to temperature shock fatigue. In addition, there may be a difference in thermal expansion coefficient between it and the base material. During the temperature shock process, due to the difference in thermal expansion coefficient, additional stress will be generated inside the solder joint, further aggravating its fatigue damage.
[0004] In addition, during the soldering process, intermetallic compounds are formed between the Sn-Ag-Cu lead-free solder alloy and the substrate. The thickness of these compounds increases over time, causing the mechanical properties at the interface to be severely weakened, thus affecting the mechanical fatigue life of the solder joint. Summary of the invention
[0005] The object of the present invention is to overcome the deficiencies of the prior art and provide a high fatigue resistance solder based on SnAgCu alloy having good mechanical fatigue resistance and temperature shock fatigue resistance.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a high fatigue resistance solder based on SnAgCu alloy, characterized in that it is composed of the following components in weight percentage: Ag 0.1-5.0%, Cu 0.1-1.0%, In 1-5%, Bi1-5%, Sb 1-6%, Ti0.001-0.5%, Nb 0.001-0.3%, Cr 0.005-0.1%, Ni 0.05-0.1%, Mo 0.005-0.2%, Co0.005-0.1%, B 0.001-0.01%, and the balance is Sn and unavoidable impurities;
[0008] The preparation method of the solder comprises the following steps:
[0009] S1. Put SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo and B into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt it at 600-650° C. in an argon environment, and take out the sample after it is cooled to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy;
[0010] S2. Put the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and In single substance into a quartz crucible, melt them in an argon environment at a temperature of 300-350°C, keep them warm and cool them with the furnace to obtain the high fatigue resistance solder based on the SnAgCu alloy.
[0011] The present invention adds components of In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B to the SnAgCu alloy. Adding elements such as Bi, Sb and Ti can affect the microstructure of the solder joint, increase the types and quantities of intermetallic compounds (IMCs), thereby improving the strength and toughness of the solder joint, and indirectly improving the impact fatigue resistance of the solder joint.
[0012] Adding Ni, Co, and Cr elements can improve the alloy's thermal fatigue resistance, slow down the growth rate of IMC, and reduce the thermal fatigue crack growth rate when serving at high temperatures, thereby improving the thermal stability of the solder joint. Ni and Co elements can also form solid solutions to increase the hardness of the alloy, while Mo, Nb, Ti, etc. may form dispersed particles or compounds to hinder the expansion of cracks.
[0013] It should be noted that although the addition of Bi can significantly reduce the growth rate of IMC at the LASAC / Cu interface, thereby improving the anti-aging performance of the solder joint, the formation of the InBi phase may lead to embrittlement of the solder joint interface and affect the reliability of the solder joint. This is because the InBi phase may form at the solder joint interface, increasing the brittleness of the interface, which can easily lead to the fracture of the solder joint during mechanical fatigue or temperature shock fatigue.
[0014] Here is what each element does:
[0015] The solid solution strengthening effect of Bi in solder alloy can improve its tensile strength and have a positive impact on fatigue resistance.
[0016] The addition of In can inhibit the growth of intermetallic compounds (IMC) at the interface, help maintain interface stability, and thus improve the fatigue resistance of the solder alloy. If the In content is too low, the effect of refining the structure and improving wettability cannot be achieved, thereby affecting the mechanical fatigue resistance and temperature shock fatigue resistance of the solder joint. When the addition of In exceeds 5.0%, a large number of blocky IMCs appear in the matrix of the alloy after high-temperature aging, which leads to a decrease in the plasticity of the material, thereby affecting its fatigue resistance. At the same time, too high an In content may cause the oxidation resistance of the solder to decrease, affecting the stability and reliability of the solder joint in a high temperature environment. Therefore, an appropriate amount of In can improve the tensile strength and shear strength of the solder alloy, thereby enhancing its fatigue resistance.
[0017] The addition of Sb can refine the β-Sn grains in the solder alloy and make the Ag3Sn phase develop from coarse needles to fine spheres with a more uniform distribution. This refinement and uniform distribution helps to improve the fatigue resistance of the solder alloy, because the smaller grain size can provide more grain boundaries, thereby hindering the movement of dislocations and improving the fatigue resistance of the material. The addition of Sb can reduce the undercooling of the solder, which helps the solder alloy to form a finer and more uniform microstructure during the solidification process, thereby improving its fatigue resistance. The addition of Sb can improve the wettability of the solder alloy, reduce the contact angle, and increase the spreading area, which helps to form better solder joints. In addition, the addition of Sb can also improve the melting characteristics of the alloy and reduce the melting range, which helps to reduce the porosity and hot tearing tendency during the welding process.
[0018] As a microalloying element, Ti can refine the austenite grains by precipitating Ti(C,N) phase, thereby obtaining fine martensite laths, which helps to improve the strength of the solder alloy.
[0019] As a microalloying element, Nb can refine the grains in the solder alloy through precipitation phase, thereby improving the strength of the solder alloy. At the same time, the addition of Nb increases the content of MC-type precipitation phase and optimizes the size distribution of the precipitation phase, thereby improving the strength of the material. The addition of Nb will increase the tensile strength and hardness of the solder alloy, and help the solder alloy resist the generation and expansion of cracks when subjected to cyclic loads, thereby improving its fatigue resistance. The addition of Nb helps to inhibit the growth of Cu grains, thereby refining the microstructure of the alloy. If the Nb content is too low, the growth of grains cannot be effectively inhibited, resulting in a decrease in the mechanical properties of the alloy, which in turn affects its fatigue resistance. Excessive addition of Nb may increase the brittleness of the solder alloy, which in turn reduces its fatigue resistance. Therefore, the appropriate addition of Nb helps to improve the mechanical properties of the solder alloy, including strength and toughness, thereby enhancing its fatigue resistance.
[0020] The addition of Cr can effectively improve the oxidation resistance of solder. On the surface of molten solder, Cr is easy to generate Cr2O3. This oxide layer can improve the oxidation resistance of solder, thereby indirectly improving the fatigue resistance of solder at high temperature. After adding Cr to the solder alloy, it was found through room temperature tensile test and high temperature aging treatment that the addition of Cr improves the plasticity of the alloy. This shows that the addition of Cr can improve the high temperature reliability of the solder alloy, thereby improving its fatigue resistance.
[0021] As an alloying element, Ni can refine the grains in the solder alloy and improve the strength of the solder alloy through solid solution strengthening and precipitation strengthening mechanisms. Sb, In and Ni can make intermetallic compounds (IMCs) more evenly distributed in the Sn matrix, thereby refining the microstructure and improving the tensile strength of the solder alloy.
[0022] Mo is a commonly used alloying element that can improve the high temperature strength of the alloy without significantly reducing the plasticity of the alloy. This is beneficial for the fatigue resistance of the solder alloy in high temperature environments, because the solder joint needs to maintain a certain strength and stability during thermal cycling. The addition of Mo can improve the thermal corrosion resistance of the solder alloy, especially in an oxygen-containing environment. This helps the solder joint maintain its performance in an environment where high temperature and corrosive media coexist, reducing fatigue failures caused by corrosion.
[0023] The addition of Co can inhibit the excessive growth of intermetallic compounds (IMC) in the solder alloy matrix and refine the alloy structure, thereby improving the fatigue resistance of the solder joint. Tests have shown that adding trace amounts of Co can improve the thermal fatigue stability of the solder joint. Moreover, by reacting with Sn to promote the rapid melting of Co, the alloy component distribution can be optimized and the grain structure can be refined, further improving fatigue resistance.
[0024] Boron has a low solubility in alloys, so it tends to segregate at grain boundaries. This segregation can change the local chemical environment of the grain boundaries, thereby affecting the stability and strength of the grain boundaries. It is precisely because of the addition of B that the strength of the grain boundaries is improved, thereby improving the fatigue life of the solder alloy under cyclic loading. At the same time, the segregation of boron can reduce the segregation of harmful impurity elements at the grain boundaries, thereby purifying the grain boundaries. At high temperatures, boron can form stable carbides or borides, which have good thermal stability and can improve the performance of the alloy in high temperature environments.
[0025] In the preparation process of the solder alloy of the present invention, Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy is first prepared, and then In is added to avoid forming a brittle InBi phase and avoiding cracks or fractures caused by external forces. It can also reduce the growth rate of the intermetallic compound at the SnBiIn / Cu interface to maintain the structural stability at the interface, thereby enhancing the interfacial bonding force, slowing down creep deformation, improving the creep resistance of the solder alloy, and thus improving its fatigue resistance. When adding In (indium) to the SnAgCu alloy, it is necessary to cool it down, mainly because the melting point of indium is relatively low, only 156.61°C. Cooling down and adding can avoid excessive volatilization or oxidation of indium at high temperatures, and also help control the solidification process of the alloy to ensure that indium can be evenly distributed in the alloy.
[0026] Preferably, the high fatigue-resistant solder based on SnAgCu alloy is composed of the following components in weight percentage: Ag 0.5-2.0%, Cu 0.8-1.0%, In 1-3%, Bi 1-2%, Sb2-4%, Ti 0.1-0.3%, Nb 0.1-0.3%, Cr 0.005-0.008%, Ni 0.08-0.1%, Mo 0.005-0.1%, Co 0.005-0.008%, B 0.005-0.01%, and the balance is Sn and unavoidable impurities.
[0027] More preferably, the high fatigue resistance solder based on SnAgCu alloy consists of the following components in weight percentage: Ag 1-1.7%, Cu 0.9-1.0%, In 1-2%, Bi 1-1.5%, Sb 2-3%, Ti 0.1-0.2%, Nb 0.2-0.3%, Cr 0.005-0.006%, Ni 0.08-0.09%, Mo 0.007-0.1%, Co 0.005-0.006%, B0.006-0.01%, and the balance is Sn and unavoidable impurities.
[0028] Most preferably, the high fatigue resistance solder based on SnAgCu alloy consists of the following components in weight percentage: Ag 1.5%, Cu 0.92%, In 1.2%, Bi 1.2%, Sb 2.6%, Ti 0.18%, Nb 0.21%, Cr 0.005%, Ni 0.08%, Mo 0.009%, Co 0.005%, B 0.007%, and the balance is Sn and unavoidable impurities.
[0029] Preferably, the method for preparing the SnCuCo alloy comprises the following steps:
[0030] Sn, Cu and Co are placed in a quartz crucible respectively, and the quartz crucible is placed in a vacuum induction furnace and melted at 990-1000°C in an argon environment. After the sample is cooled, it is taken out to obtain a SnCuCo alloy. At a high temperature of 990-1000°C, Sn can promote the melting of high-melting-point Cu and Co as quickly as possible, so that Cu and Co can be more evenly distributed in the SnCuCo alloy. This uniform distribution helps to reduce component segregation and local stress concentration in the alloy, thereby improving the overall mechanical properties and fatigue resistance of the solder alloy.
[0031] Preferably, the preparation method of the SnNi alloy comprises the following steps: smelting a nickel metal block and a tin metal block at 800-900° C. in an argon atmosphere, stirring while smelting until completely melted, and after smelting is completed, casting the alloy liquid into a mold to obtain a SnNi alloy ingot.
[0032] Preferably, in the step S2 of preparing the SnAgCu alloy-based high fatigue resistance solder, the holding time is 40-60 minutes.
[0033] Preferably, the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is (1.5-2):1.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention adds In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B to the SnAgCu alloy, which can significantly improve the mechanical fatigue resistance and temperature shock fatigue resistance of the SnAgCu alloy. The addition of Bi, Sb, Ti and other elements synergistically affects the microstructure of the solder joint, increases the type and amount of intermetallic compounds (IMCs), and thus improves the strength and toughness of the solder joint. Elements such as Sb, In, Ni and Bi can synergistically improve the tensile strength and plasticity of the Sn-Ag-Cu solder. The addition of these elements helps to form more evenly distributed IMCs, thereby bringing about a combined strengthening mechanism of solid solution strengthening and precipitation strengthening. The addition of Ni, Co and Cr synergistically improves the alloy's thermal fatigue resistance, and by slowing down the growth rate of IMCs, reduces the thermal fatigue crack propagation rate when in service at high temperatures, thereby improving the thermal stability of the solder joint.
[0036] (2) In order to avoid the formation of a brittle InBi phase by directly adding In and Bi single substances, in the preparation process of the solder alloy of the present invention, the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy is first prepared, and then the In single substance is added after cooling to avoid the formation of a brittle InBi phase and avoid cracks or fractures caused by external forces. In addition, the growth rate of the intermetallic compound at the SnBiIn / Cu interface can be reduced to maintain the structural stability at the interface, thereby enhancing the interface bonding force, slowing down creep deformation, improving the creep resistance of the solder alloy, and thus improving its fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a high-magnification microscope photograph of the solder alloy of Example 1 at 500 times;
[0038] Figure 2 This is a high-magnification microscope photograph of the solder alloy of Comparative Example 13 at 500 times;
[0039] Figure 3 This is a high-magnification microscope photograph of the solder alloy of Comparative Example 14 at 500 times;
[0040] Figure 4 This is a high-magnification microscope photograph of the solder alloy of Comparative Example 16 at 500 times. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0042] The purity of the metal elements used in the examples and comparative examples is greater than 99.9%.
[0043] Other materials and reagents, unless otherwise specified, can be obtained from commercial sources.
[0044] Examples 1 to 7 and Comparative Examples 1 to 14
[0045] The components of the solder alloys of Examples 1 to 7 and Comparative Examples 1 to 14 are shown in Table 1.
[0046] Table 1 Composition of solder alloys of Examples 1 to 7 and Comparative Examples 1 to 14
[0047]
[0048]
[0049]
[0050] The preparation method of the solder alloy of Examples 1 to 7 and Comparative Examples 1 to 14 comprises the following steps:
[0051] S1. Put SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo and B into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt them at 650°C in an argon environment. After the sample is cooled, take it out to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy; wherein the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is 1.8:1.
[0052] S2. Put the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and In single substance into a quartz crucible, melt them in an argon environment at a temperature of 350°C, keep them warm for 40 minutes and then cool them with the furnace to obtain the high fatigue-resistant solder based on the SnAgCu alloy.
[0053] The SnCuCo alloy preparation method comprises the following steps:
[0054] Sn, Cu and Co were placed in quartz crucibles respectively, and the quartz crucibles were placed in a vacuum induction furnace and smelted at 1000° C. in an argon environment. After the sample was cooled, it was taken out to obtain a SnCuCo alloy.
[0055] The preparation method of the SnNi alloy comprises the following steps: melting a nickel metal block and a tin metal block at 900° C. in an argon atmosphere in a vacuum, stirring the metal blocks while melting until the metals are completely melted, and after the melting is completed, casting the alloy liquid into a mold to obtain a SnNi alloy ingot.
[0056] Example 8
[0057] The alloy composition ratio of Example 8 is the same as that of Example 1, and its preparation method comprises the following steps:
[0058] S1. Put SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo and B into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt them at 600°C in an argon environment. After the sample is cooled, take it out to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy; wherein the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is 1.8:1.
[0059] S2. Put the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and In single substance into a quartz crucible, melt them in an argon environment at a temperature of 350°C, keep them warm for 60 minutes and then cool them with the furnace to obtain the high fatigue-resistant solder based on the SnAgCu alloy.
[0060] The SnCuCo alloy preparation method comprises the following steps:
[0061] Sn, Cu and Co were placed in quartz crucibles respectively, the quartz crucibles were placed in a vacuum induction furnace, and smelted at 990° C. in an argon environment. After the sample was cooled, it was taken out to obtain a SnCuCo alloy.
[0062] The preparation method of the SnNi alloy comprises the following steps: melting a nickel metal block and a tin metal block at 800° C. in an argon atmosphere while stirring until the metal blocks are completely melted; after the melting is completed, casting the alloy liquid into a mold to obtain a SnNi alloy ingot.
[0063] Example 9
[0064] The difference between Example 9 and Example 1 is that in the preparation method of the solder of Example 8, the melting temperature for preparing the SnCuCo alloy is 980°C.
[0065] Example 10
[0066] The difference between Example 10 and Example 1 is that the mass ratio of Sn in the SnCuCo alloy and Sn in the SnNi alloy is 1:1.
[0067] Embodiment 11
[0068] The difference between Example 11 and Example 1 is that the mass ratio of Sn in the SnCuCo alloy and Sn in the SnNi alloy is 1.5:1.
[0069] Example 12
[0070] The difference between Example 12 and Example 1 is that the mass ratio of Sn in the SnCuCo alloy and Sn in the SnNi alloy is 2:1.
[0071] Embodiment 13
[0072] The difference between Example 13 and Example 1 is that the mass ratio of Sn in the SnCuCo alloy and Sn in the SnNi alloy is 2.5:1.
[0073] Comparative Example 15
[0074] The alloy composition ratio of Comparative Example 15 is the same as that of Example 1. The difference between Comparative Example 16 and Example 1 is that the preparation method thereof comprises the following steps:
[0075] S1. Put all the single substances of Sn, Cu, Co, Ni, Ag, Bi, Sb, Ti, Nb, Cr, Mo and B into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt them at 600-650°C in an argon environment. After the sample is cooled, take it out to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy;
[0076] S2. Put the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and In single substance into a quartz crucible, melt them in an argon environment at a temperature of 350°C, keep them warm for 40 minutes, and then cool them with the furnace to obtain a solder alloy.
[0077] Comparative Example 16
[0078] S1. Put SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo, B and In into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt them at 650°C in an argon environment. After the sample is cooled, take it out to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy; wherein the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is 1.8:1.
[0079] S2. Melt Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B in an argon environment at a temperature of 350° C., keep the temperature for 40 minutes, and then cool it in the furnace to obtain the solder alloy.
[0080] Performance Testing
[0081] 1. The tensile strength of the lead-free solder alloys prepared in each embodiment and each comparative example at 25°C and 125°C was tested by a material testing machine. The solder alloys prepared in each embodiment and each comparative example were subjected to hot air circulation treatment: after soldering, the solder alloys were circulated 1000 times under the conditions of (-40°C)-(+125°C), and the high temperature and low temperature were kept for 30 minutes respectively; the tensile strength was tested again. The test results are summarized in Table 2.
[0082] 2. The melting points of the solder alloys of each group of examples and comparative examples were measured by differential scanning calorimeter to analyze the melting temperature, and the process parameters were set according to JIS-Z3198 standard. The test results are summarized in Table 2.
[0083] Table 2 Performance data of each group of solder alloys
[0084]
[0085]
[0086] As shown in Table 1, Examples 1 to 7 explore the range of different contents of each element, among which Example 1 is the optimal example.
[0087] The melting temperature of the SnCuCo alloy in Example 9 is too low, which affects the uniformity of the SnCuCo alloy and causes the performance of the obtained solder alloy to deteriorate.
[0088] Examples 1 and 10 to 13 are intended to explore the effect of the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy on the performance. Combined with the data, it can be seen that the mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is preferably (1.5 to 2):1.
[0089] Comparative Examples 1 to 12 lack one of Ag, Cu, In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B respectively. Combined with the melting point data, it can be seen that Ag, Cu, Ti, Nb, Cr, Ni, Mo and Co will increase the melting point of the alloy, while In, Bi, Sb and B can significantly reduce its melting point. The tensile strength, fatigue resistance and thermal stability of Comparative Examples 1 to 13 are significantly lower than those of Example 1, indicating that the components of Ag, Cu, In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co, B and Sn work synergistically, thereby significantly improving the mechanical fatigue resistance and temperature shock fatigue resistance of the SnAgCu alloy.
[0090] In comparative example 13, the amount of In added is too high. Figure 2 It can be seen that a large number of blocky IMCs appear in Comparative Example 14, which leads to a decrease in the plasticity of the material, thereby affecting its fatigue resistance. At the same time, too high an In content may cause the oxidation resistance of the solder to decrease, affecting the stability and reliability of the solder joint in a high temperature environment.
[0091] In Comparative Example 14, the amount of Nb added is too high. Figure 3 It can be seen that an unstable microstructure, namely, bulky intermetallic compounds and uneven Nb distribution, is formed in the SnAgCu alloy, which may become the origin of fatigue cracks and reduce the fatigue resistance of the alloy.
[0092] Comparative Example 15 is to directly mix and melt each element to obtain a solder alloy, and its performance is significantly reduced compared with Example 1. It shows that the present invention pre-alloys SnCuCo alloy and SnNi alloy and then adds other metal elements for mixing, so that the alloy elements can be distributed more evenly in the alloy, and reduce the problem of uneven mixing that may occur when the elements are directly mixed. This uniformity can improve the consistency and reliability of the solder alloy, and can also reduce the phase interface in the alloy and the stress concentration caused by the phase interface, thereby improving its fatigue resistance and thermal stability. At the same time, pre-alloying can lead to a finer and more uniform microstructure, which helps to improve the mechanical strength of the alloy. Fine grains can hinder the movement of dislocations, thereby improving the yield strength and tensile strength of the material.
[0093] Comparative Example 16 is to directly mix SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo, B and In, and its performance is significantly reduced. Figure 1 and Figure 4 It can be seen that the solder alloy of Example 1 is first made into Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and then mixed with In, so it does not have a brittle InBi phase, while the SEM image of Comparative Example 16 shows an InBi phase, and the distribution of the intermetallic compound is uneven. Therefore, the preparation method of the present invention can avoid the formation of a brittle InBi phase and avoid being easily affected by external forces and causing cracks or fractures. It can also reduce the growth rate of the intermetallic compound at the SnBiIn / Cu interface to maintain the organizational stability at the interface, thereby enhancing the interface bonding force, slowing down creep deformation, and improving the creep resistance of the solder alloy, thereby improving its fatigue resistance.
[0094] In summary, the present invention adds In, Bi, Sb, Ti, Nb, Cr, Ni, Mo, Co and B to the SnAgCu alloy, and uses a specific preparation method to obtain a solder alloy with good mechanical fatigue resistance and temperature shock fatigue resistance.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high fatigue resistance solder based on SnAgCu alloy, characterized in that: The invention is composed of the following components in weight percentage: Ag 0.1-5.0%, Cu 0.1-1.0%, In 1-5%, Bi 1-5%, Sb 1-6%, Ti0.001-0.5%, Nb 0.001-0.3%, Cr 0.005-0.1%, Ni 0.05-0.1%, Mo 0.005-0.2%, Co0.005-0.1%, B 0.001-0.01%, and the balance is Sn and unavoidable impurities; The preparation method of the solder comprises the following steps: S1. Put SnCuCo alloy, SnNi alloy, Ag, Bi, Sb, Ti, Nb, Cr, Mo and B into a quartz crucible, put the quartz crucible into a vacuum induction furnace, and melt it at 600-650° C. in an argon environment, and take out the sample after it is cooled to obtain Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy; S2. Put the Sn-Cu-Co-Ni-Ag-Bi-Sb-Ti-Nb-Cr-Mo-B alloy and In single substance into a quartz crucible, melt them in an argon environment at a temperature of 300-350°C, keep them warm and cool them with the furnace to obtain the high fatigue resistance solder based on the SnAgCu alloy.
2. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: The invention is composed of the following components in weight percentage: Ag 0.5-2.0%, Cu 0.8-1.0%, In 1-3%, Bi 1-2%, Sb2-4%, Ti 0.1-0.3%, Nb 0.1-0.3%, Cr 0.005-0.008%, Ni 0.08-0.1%, Mo0.005-0.1%, Co 0.005-0.008%, B 0.005-0.01%, and the balance is Sn and unavoidable impurities.
3. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: It is composed of the following components in weight percentage: Ag 1-1.7%, Cu 0.9-1.0%, In 1-2%, Bi 1-1.5%, Sb 2-3%, Ti 0.1-0.2%, Nb 0.2-0.3%, Cr 0.005-0.006%, Ni 0.08-0.09%, Mo0.007-0.1%, Co 0.005-0.006%, B 0.006-0.01%, and the balance is Sn and inevitable impurities.
4. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: It is composed of the following components in weight percentage: Ag 1.5%, Cu 0.92%, In 1.2%, Bi 1.2%, Sb 2.6%, Ti 0.18%, Nb 0.21%, Cr 0.005%, Ni 0.08%, Mo 0.009%, Co 0.005%, B 0.007%, and the balance is Sn and inevitable impurities.
5. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: The preparation method of the SnCuCo alloy comprises the following steps: The SnCuCo alloy is obtained by melting Sn, Cu and Co in an argon atmosphere at 990-1000°C.
6. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: The preparation method of the SnNi alloy comprises the following steps: melting a nickel metal block and a tin metal block at 800-900° C. in an argon atmosphere, stirring the metal blocks while melting until the metals are completely melted, and after the melting is completed, casting the alloy liquid into a mold to obtain a SnNi alloy ingot.
7. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: The insulation time in step S2 is 40-60 minutes.
8. The SnAgCu alloy-based high fatigue resistance solder according to claim 1, characterized in that: The mass ratio of Sn in the SnCuCo alloy to Sn in the SnNi alloy is (1.5-2):1.
Citation Information
Patent Citations
Electroconductive material, and connection method and connection structure using same
CN103796788A
SnBiAgCu high-reliability lead-free solder alloy
CN108994480A
SAC105 solder alloy and preparation method thereof
CN116275686A
Method for obtaining high-reliability lead-tin-bismuth-silver-free solder through multi-element alloying
CN118002978A
Heat-fatigue-resistant high-reliability lead-free solder alloy and application thereof
CN118559279A